CORRELATION ANALYSIS OF ATTITUDE, MOTIVATION, JOB SATISFACTION, AND ORGANIZATIONAL CULTURE TO THE PERFORMANCE OF MEKAR SAI COOPERATIVE EMPLOYEES - Dwi Herinanto; Miswan Gumanti; Yoeyong Rahsel (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study aims to test and analyze the correlation of attitudes, motivation, satisfaction, and organizational culture on the performance of employees of KSP Mekar Sai Bandar Lampung. This study is quantitative research with the subjects are employees of KSP Mekar Sai, and the population is 38 employees of KSP Mekar Sai. Based on the four independent variables studied, three variables are weak correlation between each variable Attitude, Satisfaction, and Organizational Culture on the Employee Performance of KSP Mekar Sai. There is a correlation between Attitudes to the Performance as indicated by the Spearman correlation coefficient and Kendall's correlation coefficient of 0.397. There is a weak correlation between motivation and performance of KSP Mekar Sai employees by Spearman's correlation coefficient of -0.168 and Kendall's correlation coefficient of -0.166. The correlation coefficient is negative, it means that if employee motivation increases, the resulting performance decreases. There is a very weak correlation between job satisfaction and performance, as indicated by the Spearman correlation coefficient and Kendall's correlation coefficient of 0.00. There is a weak correlation between Organizational Culture and Performance as indicated by the Spearman correlation coefficient of 0.260 and Kendall's correlation coefficient of 0.257. The results of this study are a momentary assessment when the research is carried out so that research results can change for different situations and conditions if carried out by other researchers. Keywords: attitude, motivation, satisfaction, organizational culture, performance